Pengaruh Struktur Kepemilikan dan Keputusan Keuangan terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur yang Listing di Bursa Efek Jakarta) - Andi Nirwana Nur (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research was conducted based on the idea that the success of company is very much determined by the quality of the financial decision taken by the financial managers concerned to reach the company oibjectives, i.e. increasing the prosperity of the company owners (the increase of company value). The objectives of the study are: (1) to examine and analyze the influence of stock ownership structure on investment decision, funding, dividend and company value, (2) to examine and analyze the influence of investment decision on funding decision dividend decision and company value, (3) to examine and analyze the influence of funding decision dividend decision and company value, (4) to examine and analyze the influence of dividend decision on investment decision and company value at the manufacturing company registered at Indonesian Stock Exchange This research analyses the influence among the research variables and therefore it is categorized as explanatory research. The Population of the research covers 343 manufacturing industrial company registered in Indonesian Stock Exchange mfrom 2002 to 2006. The sample of the research is 102 companies categorized into 19 industrial types. In selecting the sample, purposive influence technique was employed and SEM (Structural Equationm Model) was used to analyze data. The result of the study showed that: (1) the structure of stock ownership gave significant positive influence to investment decision, funding decision, dividend decision and company value, (2) investment decision gave significant influence to funding decision and company value (3) funding decision gave significant influence to dividend decision, (4) dividend decision gave significant influence to investment decision. Meanwhile, the funding decision and dividend decision did not gave significant influence to company value.